2019
DOI: 10.3389/fnins.2019.01149
|View full text |Cite
|
Sign up to set email alerts
|

Progress of Research on Exosomes in the Protection Against Ischemic Brain Injury

Abstract: Exosomes, as a type of extracellular vesicle (EV), are lipid bilayer vesicles 20–100 nm in diameter that can cross the blood-brain barrier. Exosomes are important transport vesicles in the human body that participate in many conduction pathways and play an important physiological role. Because of their high biocompatibility and low immunogenicity and toxicity, exosomes have attracted increasing attention as an attractive drug delivery system. This article reviews the relevant studies that have shown that exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
(48 reference statements)
0
21
1
Order By: Relevance
“…Notably, in the MSC-derived exosomes protein component, we identified a high level of mBDNF. Numerous studies showed that exosomes carry different neuronal proteins and that they can cross the blood-brain barrier 89. However, till now, it was not clear whether BDNF was present in the exosomes and the soluble component of CM, and, interestingly, in our experimental condition, we found that both exosomal fractions and soluble CM contains high levels of mBDNF, with exosomes particularly endowed of this neurotrophin.…”
contrasting
confidence: 50%
“…Notably, in the MSC-derived exosomes protein component, we identified a high level of mBDNF. Numerous studies showed that exosomes carry different neuronal proteins and that they can cross the blood-brain barrier 89. However, till now, it was not clear whether BDNF was present in the exosomes and the soluble component of CM, and, interestingly, in our experimental condition, we found that both exosomal fractions and soluble CM contains high levels of mBDNF, with exosomes particularly endowed of this neurotrophin.…”
contrasting
confidence: 50%
“…Exosomes are widely involved in the regulation of OS [ 48 , 49 ] and pathophysiological regulation of various cells; cellular pathophysiological processes include signal transduction, antigen presentation, and immune response [ 50 , 51 ]. Many of the previously conducted studies attempted to provide a detailed summary of the biogenesis of exosomes [ 52 , 53 , 54 ]. Figure 1 provides an illustration of exosome secretion under OS.…”
Section: Exosome-regulated Os Responses After Myocardial Ischemiamentioning
confidence: 99%
“…Conversely, in normal circumstances EVs are important in tissue homeostasis and organogenesis [ 103 ].…”
Section: Mechanism Of Interaction In the Biological Environmentmentioning
confidence: 99%
“…Relevant studies show that exosomes produced by neurons, oligodendrocytes, astrocytes, and microglia have a key role in the protection and repair of brain tissue [ 105 ]. They could protect neurons by inhibiting neuronal apoptosis, modulate axon reconstruction and neurogenesis through vascular regeneration, and increase synaptic vesicle release [ 103 ]. For example, microglia-derived EVs can alleviate acute inflammatory responses by converting immature IL-1b into a biologically active molecule; regulate the excitation inhibition balance via the endocannabinoids content; and reduce the levels of amyloid-β, a neurotoxic peptide linked to Alzheimer’s disease [ 106 ].…”
Section: Mechanism Of Interaction In the Biological Environmentmentioning
confidence: 99%